The Bible and borders : hearing God's word on immigration - Carroll R., M. Daniel (Grand Rapids, MI. Brazos Press, 2020)
"With so many people around the globe migrating, how should Christians and the church respond? Leading Latino-American biblical scholar M. Daniel Carroll R. (Rodas) helps readers understand what the Bible says about immigration, offering accessible, nuanced, and sympathetic guidance for the church. After two successful editions of Christians at the Border, and having talked and written about immigration over the past decade, Carroll has sharpened his focus and refined his argument to make sure we hear clearly what the Bible says about one of the most pressing issues of our day. He has reworked the biblical material, adding insights and broadening the frame of reference beyond the US. As Carroll explores the surprising amount of material in the Old and New Testaments that deals with migration, he shows how this topic is fundamental to the message of the Bible and how it affects our understanding of God and the mission of the church."--
"My father was a wandering Aramean" : stories of migration in the Old Testament -- "You are to love those who are foreigners" : Old Testament law and the sojourner -- Entertaining angels unawares : hospitality for the stranger in the New Testament -- Epilogue: The scriptures and the future
Revision and expansion of Christians at the border
Includes bibliographical references and indexes
Keywords: Emigration and immigration -- Biblical teaching; Emigration and immigration in the Bible; Emigration and immigration -- Religious aspects -- Christianity; Hospitality -- Biblical teaching